2017
DOI: 10.1002/cpdd.349
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Pharmacodynamics, Pharmacogenomics, Safety, and Tolerability of Avatrombopag in Healthy Japanese and White Subjects

Abstract: Avatrombopag, an orally administered, small-molecule thrombopoietin receptor (c-Mpl) agonist, is currently in clinical development for the potential treatment of severe thrombocytopenia in patients with chronic liver disease undergoing an elective procedure. The objectives of this study were to characterize and compare the pharmacokinetics (including the food effect) and pharmacodynamics (platelet count) of avatrombopag following single doses in Japanese and white subjects. Following single dosing under fasted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 12 publications
1
49
0
Order By: Relevance
“…Therefore, avatrombopag is recommended to be taken with a meal. Increases in platelet count are evident as early as 3–5 days after avatrombopag administration, and the highest changes in platelet count were observed by approximately 6–10 days . The safety and tolerability of avatrombopag were confirmed up to single doses of 80 mg in healthy subjects.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Therefore, avatrombopag is recommended to be taken with a meal. Increases in platelet count are evident as early as 3–5 days after avatrombopag administration, and the highest changes in platelet count were observed by approximately 6–10 days . The safety and tolerability of avatrombopag were confirmed up to single doses of 80 mg in healthy subjects.…”
Section: Introductionmentioning
confidence: 70%
“…Avatrombopag showed linear pharmacokinetics (PK) and increases platelet count in a dose‐dependent manner across a range of 20 mg to 60 mg dose in healthy subjects . Following single dosing under fasted and fed conditions, mean peak concentrations occurred at 6–8 h and subsequently declined with a half‐life of 16–19 h in healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Avatrombopag was generally well tolerated in all of these clinical studies (Bussel et al , ; Jurczak et al , ; Terrault et al , ). There has been no evidence for increased thromboembolic events, hepatotoxicity (Terrault et al , ) or significant food interactions with avatrombopag (Nomoto et al , ) reported in these studies.…”
mentioning
confidence: 78%
“…The reduced incidence of hepatic events and the lack of dietary interactions in healthy subjects from one study (Nomoto et al , ), may serve to distinguish avatrombopag from eltrombopag clinically. Such comparisons, however, clearly suffer from a lack of direct comparison of the two drugs in a single clinical trial in healthy subjects, or in patients with CLD or ITP.…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab can be considered, but it often takes several weeks to work. A TPO-RA can be tried; we favor romiplostim owing to its higher potency [43][44][45] and recommend administration of high-dose treatment upfront (5-10 µg/kg for 1-2 doses). This requires continued patience as TPO-RAs do not work immediately and require a minimum of 5 to 7 days before an effect is seen.…”
Section: Management Of Nonresponding Patients In the Initial/ Acute Smentioning
confidence: 99%